Effect of self-efficacy enhancement on successful exclusive breastfeeding among primiparous mother - Janjornmanit, Busakorn; Vongorn, Suparak; Krikitrat, Preeyakamon (Journal of Nakornping Hospital, 2025)
Primiparous mothers may lack knowledge and experience to breastfeed their infants. It may affect their confidence in exclusive breastfeed. Primiparous mothers with low breastfeeding self-efficacy may have unsuccessful exclusive breastfeeding. Objective: To compare the success of exclusive breastfeeding at 6 weeks postpartum among primiparous mothers who received self-efficacy enhancement and who received routine nursing care. Study method: This research was quasi-experimental research with two groups posttest only design. The study included primiparous mothers who were admitted to the postpartum care unit and had postpartum checkups at Nakornping Hospital, Chiang Mai, from October 2023 to March 2024. The experimental group (25 cases) received the breastfeeding self-efficacy enhancement plan, in which the research promoted individual self-efficacy, approximately 45 minutes three times per day after delivery, the control group (25 cases) received routine nursing care. Data were analyzed using descriptive statistics, Chi-square test, Fisher exact test and Mann-Whitney U test. Results: The primiparous mothers in the experimental and control groups had an average age of 23.64 + 2.96 years and 23.64 + 3.04 years. The experimental and control groups had a high school education (68%, 72%), were employed (52%, 72%), and had an income of 5,001-10,000 Baths (56%, 56%) of these were no significant differences. The primiparous mothers in the experimental group had statistically significant higher exclusive breastfeeding rates at 6 weeks postpartum period than those in the control group. (100%, 80%, p < 0.001). The experimental group after participating in the effect of self-efficacy enhancement program were significantly higher than before participation 57.68 + 3.36 and 28.68 + 6.48 (p < 0.001). Conclusion: The results of this study found that the effect of self-efficacy enhancement on exclusive breastfeeding among primiparous mothers can increase success in exclusive breastfeeding among primiparous mothers. Therefore, nurses should deploy this practice to achieve a national target to get a successful exclusive breastfeeding.